Carbon nanotube-based electrochemical sensors for quantifying the 'heat' of chilli peppers: the adsorptive stripping voltammetric determination of capsaicin. - Kachoosangi, RT; Wildgoose, G; Compton, R (2008)
A sensitive electroanalytical methodology for the determination of capsaicin using adsorptive stripping voltammetry (AdsSV) at a multiwalled carbon nanotube modified basal plane pyrolytic graphite electrode (MWCNT-BPPGE) is presented. This analytical method is then further developed using a multiwalled carbon nanotube screen-printed electrode (MWCNT-SPE) demonstrating the proof-of-concept that this approach can easily be incorporated into a sensing device which is both facile to use and inexpensive to produce. Capsaicin is the chemical responsible for the hot taste of chilli peppers, and measuring the concentration of capsaicin is an indicator of how hot any given chilli pepper, hot sauce and other related foodstuffs are. Standard additions plots for AdsSV of capsaicin at open circuit potential at a MWCNT-BPPGE exhibits two linear ranges, from 0.5 to 15 microM and from 15 to 60 microM. Using the first range of calibration curve, a detection limit of 0.31 microM (based on 3sigma) is obtained. The plot of standard additions of capsaicin determined using the disposable MWCNT-SPE shows a linear range between 0.5 and 35 microM and a detection limit of 0.45 microM. MWCNT-BPPGE and MWCNT-SPE are successfully utilized for the determination of capsaicin in real samples, such as a few commercially available hot pepper sauces, and the determined values are in excellent agreement and correlation with the average Scoville unit values reported in the literature for these sauces. To the best of our knowledge, this is the first electroanalytical method using MWCNT-BPPGE or MWCNT-SPE reported for the determination of capsaicin. This method offers advantages such as precision and objectivity over the well-known but potentially subjective Scoville method (based on organoleptic testing by human tasting panels) and is facile and inexpensive compared to existing HPLC methods.